Menganalisis Implementasi Konstruksi Berpikir Historis dalam Mata Kuliah Program Studi Pendidikan Sejarah di Universitas Simalungun - Hutauruk, Ahmad Fakhri; Ginting, Andres M.; Arent, Ease; Dabukke, Lamser (Medan Resource Center, 2024)
This study aims to analyze the implementation of historical thinking construction in courses within the History Education Study Program at Simalungun University. Historical thinking is an essential skill that history students must master, encompassing the understanding of chronology, cause-effect analysis, and the interpretation of historical events' meaning in the context of the past and their relevance to the present. This research employs a qualitative approach with a case study method. Data were collected through observations, interviews with lecturers and students, and document analysis such as syllabi and coursework. The findings indicate that the implementation of historical thinking is not yet fully optimal. Most teaching focuses on memorizing the chronology of events, figures, and places without involving in-depth analysis or connecting events to broader contexts. For instance, common assignments include summarizing readings or creating concept maps, which tend to insufficiently challenge students' skills in interpretation and critical thinking. However, in some courses, such as Indonesian History, lecturers have made efforts to use reflective approaches, such as analytical discussions on the impact of colonialism on local social dynamics. The main obstacles identified are a lack of in-depth understanding of the concept of historical thinking among both lecturers and students, as well as limited access to relevant and contextual learning resources. Therefore, this study recommends developing training for lecturers on implementing historical thinking-based teaching strategies, increasing access to learning resources that support historical analysis, and designing more challenging assignments to enhance students' critical thinking skills.